UPAYA PENCEGAHAN TINDAK PIDANA PERDAGANGAN ORANG (TRAFFICKING) - WIDIASTUTI, TRI WAHYU (Universitas Slamet Riyadi, 2010)
Abstract: The criminal conduct on human trafficking in Indonesia is a complex problem. Poverty and obsession of getting rich at once become the reasons why people are vulnerable to be exploited by the human trafficker. The victims of human trafficking are enforced to work in a long time and prone to suffer from physical, mental as well as sexual abuse. They also don’t have support and minimum protection from the outsider. Their health condition tends to suffer from sexual disease, alcohol and drug addiction. Keywords: criminal prevention, human trafficking.